An Optimization Approach for Semantic-based XML Schema Matching - Kim, Jaewook; Peng, Yun; Ivezik, Nenad; Shin, Junho (My University, 2011)
We propose a novel solution for semantic-based XML schema matching, taking a mathematical programming approach. This method identifies the globally optimal solution for the problem of matching leaf nodes between two XML schema trees by reducing the tree-to-tree matching problem to simpler problems of path-to-path, node-to-node, and word-to-word matching. We formulate these matching problems as maximum-weighted bipartite graph matching problems with different constraints, which are solved by different mathematical programming techniques, including integer programming and dynamic programming. Solutions to simpler problems provide weights for the next stage until the optimal tree-to-tree matching solution is obtained. The effectiveness of this approach has been verified and demonstrated by computer experiments.
Keywords: E-business; XML schema matching; maximum-weighted bipartite graph; semantic similarity; mathematical programming; UMBC Ebiquity Research Group